Fabrication of a mercury(ii) ion selective electrode based on poly-o-toluidine–zirconium phosphoborate. Issue 4 (4th January 2016) - Kaushal, Sandeep; Badru, Rahul; Kumar, Sanjeev; Mittal, Susheel K.; Singh, Pritpal
Abstract : This work covers various aspects of a new ion selective electrode for mercury(ii ) ions, designed by incorporation of poly- o -toluidine (PTD) into zirconium phosphoborate (ZrPB) ion exchanger. Abstract : This work covers various aspects of a new ion selective electrode for mercury(ii ) ions, designed by incorporation of poly- o -toluidine (PTD) into zirconium phosphoborate (ZrPB) ion exchanger. The designed sensor showed pretty good detection ability towards Hg 2+ ions in comparison to alkali, alkaline earth, transition and even some heavy metal ions. The crystallinity and morphology of the synthesized composite has been explored using X-ray diffraction, scanning electron microscopy and transmission electron microscopy. A linear near Nernstian response for Hg(ii ) ions with a slope of 28.0 mV per decade over a wide concentration range (1 × 10 −7 M to 1 × 10 −1 M) has been observed. The limit of detection is 7.08 × 10 −8 M (0.014 ppm). Moreover, the electrode showed significantly the same results in the pH range 2.5–10.0, a fast response time of 6 s and a life-time of at least 6 months without any divergence in potential. It has been successfully applied as an indicator electrode in potentiometric titrations, and quantitative estimation of Hg(ii ) ions in tap water, CFL unit waste water and thermometer unit waste.